Fluid Volume Overload and Congestion in Heart Failure: Time to Reconsider Pathophysiology and How Volume Is Assessed. (August 2016) - Miller, Wayne L.
Abstract : Volume regulation, assessment, and management remain basic issues in patients with heart failure. The discussion presented here is directed at opening a reassessment of the pathophysiology of congestion in congestive heart failure and the methods by which we determine volume overload status. Peer-reviewed historical and contemporary literatures are reviewed. Volume overload and fluid congestion remain primary issues for patients with chronic heart failure. The pathophysiology is complex, and the simple concept of intravascular fluid accumulation is not adequate. The dynamics of interstitial and intravascular fluid compartment interactions and fluid redistribution from venous splanchnic beds to central pulmonary circulation need to be taken into account in strategies of volume management. Clinical bedside evaluations and right heart hemodynamic assessments can alert clinicians of changes in volume status, but only the quantitative measurement of total blood volume can help identify the heterogeneity in plasma volume and red blood cell mass that are features of volume overload in patients with chronic heart failure and help guide individualized, appropriate therapy—not all volume overload is the same.